Accurate detection of the edges in a photograph - Ahmad Abdillah Zaini (2018)
This project develops a system of finding the edges of a room in a photograph. A program would be developed to detect the relevant edges between the walls, ceiling and floor in the photograph. The program is demonstrated on an image of a cube and also on an image of a computer-generated room. The issues are discussed as reference for future work.